Social Innovation and Value Transformation in Batik Ciprat Karangpatihan Ponorogo - Zidnaa Luthfa Hudaaka (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study aims to examine how process-based social innovation facilitates value creation and value transformation within disability based social entrepreneurship. Using an exploratory qualitative approach, the research focuses on Batik Ciprat Disabilitas Karangpatihan, Ponorogo, through in-depth interviews, participant observation, and document analysis. The findings reveal that adaptive production design particularly the ciprat batik technique functions as a key mechanism for transforming disability-related limitations into creative and economic assets. The innovation generates dual value in the form of social inclusion and economic sustainability, while simultaneously producing communal value through enhanced social capital and institutional recognition at the village level. More importantly, the interaction of social, economic, and communal values enables a deeper transformation of identity, stigma, and economic independence among artisans with disabilities. This study contributes to the social entrepreneurship literature by demonstrating that value transformation emerges from process innovation rather than outcomes alone, highlighting the strategic role of inclusive work design in achieving sustainable and dignified economic participation.